2005
DOI: 10.1017/s0021932005007170
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Insufficient Milk as a Barrier to Optimal Infant Feeding: Examples From Bolivia

Abstract: In its recently adopted Global Strategy on Infant and Young Child Feeding, the World Health Assembly called for urgent action in addressing the barriers to optimal feeding practices. This paper examines mothers' concerns about milk insufficiency as a major contributor to suboptimal infant feeding decisions, using survey data from peri-urban areas of two Bolivian cities. Mothers in the lowland modernizing city of Santa Cruz were more likely than mothers in the highland traditional city of Cochabamba to express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
3
21
0
2
Order By: Relevance
“…Our finding about the phenomenon of breast milk insufficiency is consistent with previous research that has been conducted across diverse cultural norms and practices, socio‐economic status of mothers and rural and urban contexts (McCann & Bender 2006; Sacco et al. 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding about the phenomenon of breast milk insufficiency is consistent with previous research that has been conducted across diverse cultural norms and practices, socio‐economic status of mothers and rural and urban contexts (McCann & Bender 2006; Sacco et al. 2006).…”
Section: Discussionsupporting
confidence: 91%
“…2010). One of the most common reasons frequently cited by mothers in many communities throughout the world is the perception of breast milk insufficiency (Dykes & Williams 1999; McCann & Bender 2006; Sacco et al. 2006).…”
mentioning
confidence: 99%
“…For example: many societal and environmental factors such as cultural norms, hospital, home, work and community environments have been shown to impact on the rate of successful breastfeeding [12]. Another commonly reported reason for unsuccessful breastfeeding or early weaning is perceived low or insufficient breast milk supply [13]. Poor breastfeeding technique or latching leading to ineffectual milk removal, deficient mammary gland tissue and maternal hormonal imbalances can all contribute to insufficient supply of milk [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite women’s experience of insufficient breast milk production, only about five percent have a biological factor making them unable to produce enough breast milk [7,8]. Most women who experience insufficient breast milk production provide infant formula, but some women choose to latch the baby on to stimulate the breast or to seek advice from health professionals [42,43]. Dykes and Williams reported that women with experience of insufficient breast milk were dissatisfied with incorrect and conflicting advice from health professionals, and it had negative consequences for their ability to breastfeed [44].…”
Section: Discussionmentioning
confidence: 99%